2008
DOI: 10.1373/clinchem.2007.095190
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Uric Acid and the Risk of Type 2 Diabetes in a Chinese Community

Abstract: BACKGROUND:Previous cross-sectional studies have shown hyperuricemia to be prevalent among individuals with metabolic syndrome, but the evidence from prospective studies of an association between uric acid and diabetes risk is limited. We prospectively investigated the association between plasma concentrations of uric acid and the incidence of type 2 diabetes in Chinese individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 41 publications
9
98
1
1
Order By: Relevance
“…The high risk of diabetes among our study participants may be explained by older age, higher body mass index and a single measurement for case diagnosis [44].…”
Section: Discussionmentioning
confidence: 88%
“…The high risk of diabetes among our study participants may be explained by older age, higher body mass index and a single measurement for case diagnosis [44].…”
Section: Discussionmentioning
confidence: 88%
“…A cross-sectional study of a consecutive sample of 3065 staff who had undergone health examination suggested that SUA level was highest in subjects with abnormal levels of triglycerides but an abnormal range of fasting glucose did not affect the SUA level. 23 In another study, the association of triglycerides and uric acid has been persistent after full adjustment in a multiple logistic model, suggesting that triglycerides correlate independently with uric acid level. Interestingly, the association was obtained even within the normal range of serum triglycerides.…”
Section: Discussionmentioning
confidence: 95%
“…Individuals with a fasting blood sugar level 4126 mg per 100 ml and/or use of oral hypoglycaemia agents or insulin injections were defined as diabetes mellitus. 15,23 …”
Section: Definition Of Hypertension and Associated Risk Factorsmentioning
confidence: 99%